ANALISIS KINERJA PORTOFOLIO MAGIC FORMULA PADA INDEKS LQ45 DI BURSA EFEK INDONESIA - Angga Sasmitapura; Michael Michael; Sandra Faninda (Bina Ekonomi, 2022)
The rapid growth of active investors in Indonesia stock market raises awareness on the importance of investors’ skill needed in analyzing and choosing profitable stock. One of the method knows to analyze profitable stock in the market is Magic Formula introduce by Joel Grenblatt -part of value investing. Magic Formula is a method on choosing a profitable stock in a simple way based on combination of  both High Earnings Yield and High Return on Capital. The period use in this research is from 2016 – 2020. This research use LQ 45 stock listed in Indonesia Stock Exchange. This qualitative research used secondary data which is analyzed using backtesting simulation. The result of this research shows that Magic Formula’s Stock Portfolio build based on data consist of different number of stock: 15, 20, and 25 stock; combination of both high Earnings Yield and High Return on Capital. The Magic Formula’s Portfolio formed based on the LQ 45 stock has higher aritmathic average return compare to LQ 45 return and even the 15-stock-based portfolio beat the Indonesia Composite Index average return. However on the CAGR rate of return, the calculation show that the return of the Magic Formula Portfolio below the return of Indonesia Composite Index